Dietary Patterns among Urban and Rural School Teachers in Guntur District of Andhra Pradesh (Indian Journal of Public Health Research & Development, 2026)
Introduction: Urban and rural diets in India are subject to influences like income, food availability, and life styles.As school teachers are also health promoters and role models for their students and communities, this study wasset to identify the dietary patterns of urban and rural school teachers in Guntur district of Andhra Pradesh, Indiaalong with comparison of anthropometrics and Diet Related Non-Communicable Disease (DRNCDs).Methods: This descriptive study involved all teachers of five schools each from rural and urban mandals of Gunturdistrict selected by simple random sampling. A predetermined questionnaire covering various aspects of diet,socio – demographic variables and anthropometric measurements like height, weight, BMI and waist hip-ratiowere administered to each teacher after taking an informed consent. Data was entered in MS excel and presentedin tables and graphs. Important findings were subjected to tests of significance like Chi square test at 5 % Level ofSignificance.Results: Chronic non communicable illnesses were present in 27.6% of the rural teachers and 66.0% of urbanteachers (Chi square 16.5%, p value < .0001, OR 5.1, 95% CI 2.1 to 12.5). DRNCDs were present in 27 (46.6%) ruralteachers and 24 (45.3%) urban teachers.86.8% of the male teachers and 43.1% of the female teachers were obeseaccording to their BMI (Chi Square 22.93, p value
Keywords: Dietary patterns, Diet Related – Non communicable diseases (DR-NCDs), Teachers, urban, rural